Stay safe! : how you can keep out of harm's way - Nelson, Sara Kirsten (Minneapolis, MN : Lerner Pub., 2009)
Tips for dealing with threats to personal safety, whether from a bully in school or a stranger on a street corner.
Includes bibliographical references (p. 61-62) and index.
Keywords: Safety education -- Juvenile literature; Children and strangers -- Juvenile literature; Children -- Crimes against -- Prevention -- Juvenile literature; Child sexual abuse -- Prevention -- Juvenile literature; Safety; Strangers; Children -- Crimes against -- Prevention; Sexual abuse -- Prevention